سیرتِ نبوی پر استشراقی نظریات کا ناقدانہ جائزہ : "محاضراتِ سیرت" کا خصوصی مطالعہCritical Examination of Orientalists’ views on Prophetic Sīrah: A Study of “Muḥāḍrāt-e-Sīrat” (Al-Qamar, 2021)
This paper studies the response of Dr. Maḥmood Ahmed Ghāzī (1950-2010), a well-known Pakistani jurist and scholar, to the orientalists’ criticism on Sīrah of Prophet Muhammad (ﷺ), in his “Muḥāḍrāt-e-Sīrat”. The study reveals that Ghāzī has scholarly responded the orientalists’ objections on Prophetic Sīrah. He proves that orientalists’ claims such as Quran was written by Muhammad himself; the ḥadīths were unreliable; the sources of Prophetic biography were unauthentic; the Prophet after migrating to Medina became a worldly king; the Prophet belonged to an inferior clan; he adopted polygamy for his sexual desires, etc., are the results of their prejudices and misunderstandings. In many places it seems that they have distorted the facts.
Keywords: Orientalists; Sīrah, Ghazī; Muḥāḍrāt-e-Sīrat